Tinjauan Yuridis Terhadap Abandonemen (Penyerahan Hak Milik Atas Benda Pertanggungan) dalam Hal Penyelesaian Klaim Asuransi Rangka Kapal (Marine Hull Insurance) (Lex Jurnalica, 2010)
Insurance is a bilateral agreement in which the first party as an insured to pay the insurance premiums to the second party as the person who is willing to bear the losses suffered by the goods or services of value arising from the insured property. Development of marine insurance relating to the implementation of the transport or shipping is done through a sea full of marine hazards. In a sense, marine insurance is not just limited to the marine environment only, but will also include terrestrial environments and inland waters (rivers and lakes). The author uses the methods of normative research that focuses on secondary data or literature data as a primary source. From the results of research already done so authors can be concluded that the legal basis of insurance contained in the Book of Acts - Act trademark law (Commercial code), Act - Act 2 of 1992 concerning insurance undertakings. Marine insurance basically guarantees loss, damage (risk) as a result of the dangers of the sea. With the agreement of the insured's coverage then the risk is taken over by the insurer, provided that the insured must pay premiums for marine insurance. About the dangers - dangers that are borne not only limited to the hazards that occur at sea, but also about the dangers - dangers that can occur canal during transport, such as a fire hazard dipelabuhan. Basically, the insurance must have an element of the insured interests, compensation received shall be in accordance with what has been previously agreed upon closing of insurance, and payment of compensation can only be given after the loss that befell the insured. From these elements, the coverage made by the insurer and the insured would be void if the insured to speculate on the state of things - things that are not trueKeywords: Abandonemen, Marine Hull Insurance, Claim